Raising public awareness of the ecological benefits of screwpine trees through online and offline campaigns (research conducted at SDN 03 Panggarangan Village, Bayah, Banten) - Asmarantika, Rossalyn Ayu; Putranto, Teguh Dwi; Lolita, Theresia Lavietha Vivrie (Program Studi Pengembangan Masyarakat Islam, 2023)
SAPA LAUT is a sustainable campaign activity that aims to increase public awareness of the importance of maintaining the marine pandanus (screwpine plant) ecosystem in coastal areas. The method used in this activity is Participatory Action Research (PAR) with several stages. The SAPA LAUT series of activities were carried out online through Instagram for donations and dissemination of information about sea pandanus. Meanwhile, the offline campaign was carried out at SDN 3 Panggarangan. In the offline campaign, the activity was divided into 3 sessions, namely educational sessions, sea pandan planting sessions, and donation handover. As a result, a donation of Rp 7,077,000 was obtained from the online campaign, planting 300 sea pandanus tree seedlings and handing over donations to SDN 3 Panggarangan. The first activity, which was held at SDN 3 Panggarangan, Bayah, Banten, involved students and teachers of SDN 3 Panggarangan, UMN students, and volunteers of the South Lebak Mitigation Cluster (GMLS).